Long-term students’ management strategies and parental involvement in homework at the elementary level - Deslandes, Rollande; Rousseau, Michel (International Journal about Parents in Education, 2023)
This study assessed the evolution of children’s homework management strategies and their parents’ involvement in homework over a 3-year span, taking into account student gender and achievement, family structure and parent educational level. It also investigated the relationships between children’s strategies and parental help in homework. The sample consisted of 157 parent-child dyads from geographically and economically diverse regions in Quebec. The study found no link between child gender and achievement and parent educational level and reported elementary students’ homework management strategies. As children grew older, from grade 4 to grade 6, they took fewer initiatives to motivate completion of homework (monitoring motivation), to eliminate unwanted emotions, and to budget time (monitoring and controlling emotions / managing time). Parental help declined over the years, more importantly for girls than for boys. Parental help in homework seemed to foster among girls strategies in monitoring motivation and among boys, strategies in structuring their workspace at home (arranging environment), in dealing with frustration and in keeping track of the remaining available time for homework (monitoring and controlling emotions / managing time). Evidently, grade 6 students still benefit from parents being involved with their homework. Moreover, overtime findings, from grade 4 to grade 6, confirm the contribution of parental involvement in fostering desirable study habits, notably, monitoring motivation and monitoring and controlling emotion and managing time strategies. Those findings are of paramount importance in counterbalancing the observed decline in these same strategies over the 3-year span period.